Uploaded by abelardoerica2

Solution-to-Quiz-1

advertisement
Solution to Quiz 1
SET A
1
1
3
1. ∫(8π‘₯ 4/5 − 3π‘₯ 5 + 2) √π‘₯ 2 𝑑π‘₯ = ∫(8π‘₯ 4/5 − 3π‘₯ 5 + 2) π‘₯ 2/3 𝑑π‘₯
1
= 8 ∫ π‘₯ 22/15 𝑑π‘₯ − 3 ∫ π‘₯ −13/3 𝑑π‘₯ + 2 ∫ π‘₯ 2/3 𝑑π‘₯
15
1
3
3
= 8⦁ 37 π‘₯ 37/15 − 3 (− 10) π‘₯ −10/3 + 2 (5) π‘₯ 5/3 + 𝐢
=
120
37
1
6
π‘₯ 37/15 + 10π‘₯ 10/3 + 5 π‘₯ 5/3 + 𝐢
1
2. ∫ csc(5π‘₯ + 3) cot(5π‘₯ + 3)𝑑π‘₯ = − csc(5π‘₯ + 3) + 𝐢
5
3. ∫ sec 2 π‘₯ (1 + tan π‘₯) 𝑑π‘₯ = ∫ 𝑒𝑑𝑒
Let 𝑒 = 1 + tan π‘₯
𝑑𝑒 = sec 2 π‘₯ 𝑑π‘₯
1
= 2 𝑒2 + 𝐢
1
= 2 (1 + tan π‘₯)2 + 𝐢
4. ∫ π‘₯ 5 √2 − π‘₯ 3 𝑑π‘₯ = ∫ π‘₯ 3 √2 − π‘₯ 3 π‘₯ 2 𝑑π‘₯
1
= − 3 ∫(2 − 𝑒)𝑒1/2 𝑑𝑒
2
1
= − ∫ 𝑒1/2 𝑑𝑒 + ∫ 𝑒3/2 𝑑𝑒
3
3
2 2
1 2
= − 3 (3) 𝑒3/2 + 3 (5) 𝑒5/2 + 𝐢
4
2
= − 9 (2 − π‘₯ 3 )3/2 + 15 (2 − π‘₯ 3 )5/2 + 𝐢
𝑒 = 2 − π‘₯3
𝑑𝑒 = −3π‘₯ 2 𝑑π‘₯
1
− 3 𝑑𝑒 = π‘₯ 2 𝑑π‘₯
Let
π‘₯3 = 2 − 𝑒
SET B
1. ∫ (3π‘₯ 4/3 −
1
2π‘₯ 4
1
+ 5) √π‘₯ 3 𝑑π‘₯ = ∫(3π‘₯ 4/3 − 2π‘₯ 4 + 5) π‘₯ 3/2 𝑑π‘₯
1
= 3 ∫ π‘₯ 17/6 𝑑π‘₯ − 2 ∫ π‘₯ −5/2 𝑑π‘₯ + 5 ∫ π‘₯ 3/2 𝑑π‘₯
6
1
2
2
= 3⦁ 23 π‘₯ 23/6 − 2 (− 3) π‘₯ −3/2 + 5 (5) π‘₯ 5/2 + 𝐢
18
1
= 23 π‘₯ 23/6 + 3π‘₯ 3/2 + 2π‘₯ 5/2 + 𝐢
1
2. ∫ sec 2 (2 − 5π‘₯)𝑑π‘₯ = − 5 tan(2 − 5π‘₯) + 𝐢
3. ∫(1 + cot π‘₯) csc 2 π‘₯ 𝑑π‘₯ = − ∫ 𝑒𝑑𝑒
Let 𝑒 = 1 + cot π‘₯
𝑑𝑒 = −csc 2 π‘₯ 𝑑π‘₯
1
= − 2 𝑒2 + 𝐢
1
= − 2 (1 + cot π‘₯)2 + 𝐢
4. ∫ π‘₯ 3 √2 − π‘₯ 2 𝑑π‘₯ = ∫ π‘₯ 2 √2 − π‘₯ 2 π‘₯𝑑π‘₯
1
= − 2 ∫(2 − 𝑒)𝑒1/2 𝑑𝑒
1
= − ∫ 𝑒1/2 𝑑𝑒 + 2 ∫ 𝑒3/2 𝑑𝑒
2
1 2
= − 3 𝑒3/2 + 2 (5) 𝑒5/2 + 𝐢
2
1
= − 3 (2 − π‘₯ 2 )3/2 + 5 (2 − π‘₯ 2 )5/2 + 𝐢
𝑒 = 2 − π‘₯2
𝑑𝑒 = −2π‘₯𝑑π‘₯
1
− 2 𝑑𝑒 = π‘₯𝑑π‘₯
Let
π‘₯2 = 2 − 𝑒
Download